Develop Electricity Projects and Transmission lines in a 'War Footing' (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
Not available. DOI: http://dx.doi.org/10.3126/hn.v14i0.11243Hydro Nepal JournalJournal of Water, Energy and EnvironmentVol. 14, 2014, JanuaryPage:7-7